Associação Brasileira de Hematologia, Hemoterapia e Terapia Celular Consensus on genetically modified cells. VI: Accreditation process - Gil Cunha De Santis (Elsevier, 2021)
The adherence to accreditation programs proves the institutions' voluntary effort to pursue the quality and safety of their products and services by meeting internationally accepted standards audited by experts in the field, external to the service. Meeting such standards often exceeds domestic legal requirements. However, service providers are not released from complying with the legal requirements, both local and international, pertinent to the field. Accreditation programs use the precepts of the quality management system to validate and standardize processes, monitor results through quality control, proficiency testing, and indicators, and perform risk management. For cellular therapy services, the assessing agencies available in our field are the AABB/ABHH (American Association of Blood Banks/Brazilian Association of Hematology, Hemotherapy and Cellular Therapy) and FACT-JACIE (Foundation for the Accreditation of Cellular Therapy-Joint Accreditation Committee, ISCT/EBMT). Both agencies require that the accredited organization meets all the standards defined in each program. Applying services also have to establish and comply with a quality management standard that demonstrates procedural interrelationship to ensure product and service quality. This paper aims to concisely outline the essential features of those two accreditation programs, along with a brief overview of the accreditation process under each of them.